Numerical analysis in rock : sequential excavation - He, Quanquan (2016)
Underground excavation and tunneling have been solutions for sustainable urban development all over the world. However, rock as a complex engineering material, brings huge amount of uncertainties. Therefore, understanding of rock responses and analytical data is of much importance for engineers to cope with underground projects challenges. This project analyzes the behavior of rock mass of underground rock caverns under static loads by carrying out numerical analysis. Comparison is made with the result from different joint parameters and different rock bolting styles. Both stress and displacement of individual rock block will be looked into to study difference. Stress in the rock bolt in critical locations is also studied. Since discontinuous deformation analysis (DDA) has been widely applied in simulating discontinuous blocks system, it is used in this project to produce accurate and reliable results. Rock cavern models with size of 120 meters by 120 meters will be simulated in DDA.